Multivariate analysis of profitability indicators for selected companies of croatian market - Ana Perisa; Natasa Kurnoga; Martina Sopta (UTMS Journal of Economics, 2017)
In this paper, the profitability indicators are analysed for the first hundred companies of the Croatian market, which are classified according to the net profit. The profitability indicators included in the analysis are the following: EBIT margin, EBITDA margin, net profit margin, return on assets (ROA), return on invested capital (ROI) and return on capital employed (ROCE). By implementing the factor analysis, six chosen profitability indicators have been reduced to two factors, thus solving the multicollinearity problem, which is one of the prerequisites for the cluster analysis. For two extracted factors, the factor scores are calculated and used in the following cluster analysis. By implementing the cluster analysis, selected companies are grouped into clusters according to their similarity in accomplished results that are measured by profitability indicators. The hierarchical and non-hierarchical cluster analyses are conducted and resulted into two clusters where ten companies were in the first cluster, while the other ninety were in the second cluster.
Keywords: G32; 330; factor analysis; cluster analysis; profitability indicators; multivariate analysis; profit theories